On the timing and probability of presurgical teledermatology: how it becomes the dominant strategy - de Mello-Sampayo, F. (Health Care Management Science, 2022)
Health level fluctuations make the outcome of any treatment option uncertain, so that decision-makers might have to wait for more information before optimally choosing treatments, especially when time spent in treatment cannot be fully recovered later in terms of health outcome. To examine whether or not, and when decision-makers should use presurgical teledermatology, a dynamic stochastic model is applied to patients waiting for dermatology surgical intervention. The theoretical model suggests that health uncertainty discourages using teledermatology. As teledermatology becomes less cost competitive, the uncertainty becomes more dominant. The results of the model were then tested empirically with the teledermatology network covering the area served by one Portuguese regional hospital, which links the primary care centers of 24 health districts with the hospital’s dermatology department via the corporate intranet of the Portuguese healthcare system. Under uncertainty and irreversibility, presurgical teledermatology becomes the dominant strategy for younger patients and with lower probability of developing skin cancer.